Motivation in learning English according to Buddhism - Sobbong, Pattalawan; Konchai, Kanungnit (Asia Pacific Journal of Religions and Cultures, 2019)
Motivation in learning English according to Buddhism there are 2 objectives in the study 1) to study the English language teaching model 2) to strengthening motivation in learning English according to Buddhism for finding ways to teach English in various situations. This research is a qualitative research. Research tools are structured interview and questionnaire. The key informant is selected samples of 20 novice samples from Bunruangwittaya School, Pa Ko Dam Subdistrict, Mae Lao District, Chiang Rai Province. The research found that; Motivation in learning English according to Buddhism, the results of the study according to objective 1 found that students have better English learning behavior in English courses and achievement in English courses better. The results of the study according to objective 2 found that Enhancing motivation in learning English according to Buddhism such as 4 holy abiding, the 4 noble truths and 4 Iddhipada are important in organizing teaching and learning activities. Should be very stimulating and reinforcing. In organizing teaching and learning activities to achieve better results in the course.